MEDIA PEMBELAJARAN FISIKA PADA MATERI BUNYI DENGAN METODE COMPUTER ASSISTED INSTRUCTION (CAI) BERBASIS MULTIMEDIA 2D UNTUK SISWA KELAS VIII SMP N 02 LIMBANGAN - Ester Liliana karismatika (Pixel :Jurnal Ilmiah Komputer Grafis, 2017)
Technology is very instrumental in improving the quality of education, it is necessary to have media that can support the realization of effective learning activities from the school through the teaching learning process. SMP N 02 Limbangan is a school that uses modules as material for teaching, but students are less enthusiastic in learning, so the material delivered is less acceptable and well understood, and the value of the material is below the complete limit. The existence of these problems makes the writer want to participate in improving the quality of student grades through this research and development by creating a 2D multimedia-based learning media by using the Computer Assisted Intruction (CAI) method in Sound Physics Science Subjects. The results of validation from media experts are 3.2. This criterion is between 3.26 - 4.00 which is classified as a very valid category. the validation result from the material expert is 3.2. This criterion is between 3.26 - 4.00 which is classified as a very valid category. that the results of the validation of the user show the value of 3.28 is between 2.25 - 4.00 which is classified in the category of very valid.